Novel design of a high efficiency multi-bed active magnetic regenerator heat pump. (December 2021) - Dall'Olio, S.; Masche, M.; Liang, J.; Insinga, A.R.; Eriksen, D.; Bjørk, R.; Nielsen, K.K.; Barcza, A.; Vieyra, H.A.; Beek, Niels V.; Bez, H. Neves; Engelbrecht, K.; et al.
Highlights: A two-pole magnet alternately magnetizes 13 layered regenerator beds. A parallel flow circuit using solenoid valves controls the magnetic cooling cycle. At a 10.3 K span, 340 W heating power with a heating AMR COP of 6.7 was produced. A maximum second-law efficiency of 20.6 % was achieved. Abstract: The design of a rotary active magnetic regenerator heat pump device with a multi-bed concept is presented. Important design features are the rotating two-pole magnet assembly, the laminated iron ring, the 13 fixed tapered regenerator beds, and the dynamically adjustable parallel flow circuit. The optimized magnet design was developed with optimally shaped segments and optimum remanence for the desired magnetic field distribution oscillating between 0 and 1.44 T in the air gap. The iron ring was laminated to reduce the eddy currents, allowing the device to run at cycle frequencies up to 3 Hz. The design of the regenerator housing was optimized with respect to parasitic losses and even flow distribution in both directions. Employing 3.4 kg of La(Fe, Mn, Si)13 Hy (CALORIVAC HS) refrigerant and at a hot reservoir temperature of 295 K and a cycle frequency of 0.5 Hz, the heat pump achieved a maximum second-law efficiency of 20.6 %, while providing a heating load of 340 W with a heating COP of 6.7 at a 10.3 K span. The COP values presented only consider the magnetic power and ideal pump power delivered to the AMR, neglecting the pump efficiency. At 1.2 Hz, the device produced a maximum heating power of 950 W while maintaining a 5.6 K span, resulting in a heating coefficient of performance and second-law efficiency of 7.0 and 11.6 %, respectively. The performance demonstrated in this paper could be an important milestone in the development of future magnetocaloric devices. Graphical abstract: Image, graphical abstract